2022
DOI: 10.3389/fvets.2022.890585
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Jejunal Immunity and Microbial Composition of Growing-Period Tibetan Pigs and Duroc × (Landrace × Yorkshire) Pigs

Abstract: The gut microbiota plays vital roles in metabolizing nutrient, maintaining the intestinal epithelial barrier but also in modulating immunity. Host genetics and the pig breed are implicated in shaping gut microbiota. Tibetan pig is a unique native Chinese breed and has evolved to manifest a strong disease resistance. However, the immunity and microbiota of growing Tibetan (TP) pigs were still rarely understood. The jejunal immunity phenotype and microbial composition of TP and Duroc × (Landrace × Yorkshire) (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Regarding the specific genera observed in LHS farms, more that are considered detrimental bacteria were observed. Some of them related to the host, such as Solibacillus , negatively correlated with crypt depth ( 58 ); or Sporobacter , suggested to have a negative role in gut health and associated with Salmonella positive free-range pigs ( 59 , 60 ). There were also pathogens associated with ectoparasites, such as Wohlfahrtiimonas , causing several diseases in humans related to traumatic skin lesions, myiasis, wound contamination and sepsis ( 61 ); or Rickettsia , an obligate intracellular pathogen that causes diseases in humans, as well as domestic and wild animals, through vector transmission ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the specific genera observed in LHS farms, more that are considered detrimental bacteria were observed. Some of them related to the host, such as Solibacillus , negatively correlated with crypt depth ( 58 ); or Sporobacter , suggested to have a negative role in gut health and associated with Salmonella positive free-range pigs ( 59 , 60 ). There were also pathogens associated with ectoparasites, such as Wohlfahrtiimonas , causing several diseases in humans related to traumatic skin lesions, myiasis, wound contamination and sepsis ( 61 ); or Rickettsia , an obligate intracellular pathogen that causes diseases in humans, as well as domestic and wild animals, through vector transmission ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…For determination of immune indices, we following antibodies from Servicebio Technology, Wuhan, CN: rabbit anti-ZO-1 (#GB11195, 1:200), rabbit anti-1L-1β, rabbit anti-1L-6 (#GB11113 and #GB11117, 1:800), rabbit anti-1L-10 (#GB11108, 1:300), mouse anti-TLR4 (#GB11269, 1:100), rabbit anti-TLR2 (#GB11554, 1:500), and rabbit anti-MUC-2 (#GB11344, 1:1,000) primary antibodies and an HRP-conjugated goat anti-rabbit IgG (#GB23303, 1:200) as a secondary antibody. The methods were based on those reported by Yang et al ( 21 ).…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Highly diverse and complex microbiota exist in the gastrointestinal tract of pigs with distinct longitudinal, radial, and timely distributions [ 11 ]. Increasingly, studies have demonstrated that both swine genetics and gut microbial composition play crucial roles in nutrient metabolism and disease resistance [ 12 , 13 , 14 ]. The pig is one of the most omnivorous of domesticated farm animal species, which easily adapts to various plant-based feed and carcasses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%